2019
DOI: 10.1017/s1537592719000963
|View full text |Cite
|
Sign up to set email alerts
|

“I’m Not the President of Black America”: Rhetorical versus Policy Representation

Abstract: A key question in the study of minority representation is whether descriptive representatives provide superior substantive representation. Neglected in this literature is the distinction between two forms of substantive representation: rhetoric versus policy. We provide a systematic comparison of presidential minority representation along these two dimensions. Barack Obama was the first African American president, yet his substantive representation of African Americans has not been fully evaluated. Using speec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…In a departure from Harris (2012) and Price (2016), Haines et al (2019) argue that while Obama offered less rhetorical representation for African Americans on poverty and civil rights than comparable presidents, he provided more substantive representation in these areas, as evidenced by his budget proposals. However, more research is needed to test whether Obama's rhetorical representation of African Americans translated into substantive representation in areas other than poverty and civil rights.…”
Section: The Role Of Racial Cues In the Presidential Campaigns And Presidency Of Barack Obamamentioning
confidence: 99%
“…In a departure from Harris (2012) and Price (2016), Haines et al (2019) argue that while Obama offered less rhetorical representation for African Americans on poverty and civil rights than comparable presidents, he provided more substantive representation in these areas, as evidenced by his budget proposals. However, more research is needed to test whether Obama's rhetorical representation of African Americans translated into substantive representation in areas other than poverty and civil rights.…”
Section: The Role Of Racial Cues In the Presidential Campaigns And Presidency Of Barack Obamamentioning
confidence: 99%
“…In addition, Irene Bloemraad (2013, 654-5) considers descriptive representation "a measure of the acceptance of a particular group by those in the majority" while having "real consequences for a minority group's substantive representation … influencing the allocation of public resources such as public contracts or social benefits." Moreover, minority "representatives may provide worse rhetorical representation, but nonetheless offer better policy representation than their [majority] counterparts," as was recently demonstrated in the case of the first African American president of the United States (Haines, Mendelberg, andButler 2019, 1039). Other benefits of higher descriptive representation include a positive change in the majority's beliefs about a minority (Chauchard 2014) and lower risk of civil conflict (Cederman, Weidmann, and Gledistch 2011).…”
Section: Discussionmentioning
confidence: 95%
“…Accordingly, studies of presidential rhetoric, including during Barack Obama's tenure, have identified relatively few references to racial struggle or inequality (Gillion, 2016;Haines et al, 2019) in their rhetoric. The emphasis instead has been on unifying rhetoric that de-emphasizes the significance of race and can undermine efforts to promote racial equality (Harris, 2012), although with significant variation, nuance, and evolution over time (Price, 2016).…”
Section: Equality and Individualism In Elite Rhetoricmentioning
confidence: 99%